Fan tourism and fan tourists: discussion on definitions and research issues - Krupa, Joanna; Nawrocka, Elżbieta (Turyzm/Tourism, 2020)
The purpose of the article is to systematize the concepts of fan tourism and fan tourists and an attempt has also been made to identify the profile of a fan tourist. There are certain research gaps in terms of defining the concept itself, therefore the authors have decided to investigate this. Literature analysis and criticism as well as synthesizing ideas were methods used in this work. The article presents the characteristics of fan tourism and a description of a fan tourist using psychological, social and economic criteria identified on the basis of a literature investigation. The following attributes were distinguished: the main motive of activity, emotional involvement, ‘extreme’ support, commitment to ideas, sympathy towards ideas, personal attendance at an event and the nature of a consumer or a prosumer when a fan tourist participates in an event personally. The concepts of a fan in general, fanatic and sports fan (kibic) were used in the process of identifying the characteristics of a fan tourist.